2002
DOI: 10.1212/wnl.59.1.92
|View full text |Cite
|
Sign up to set email alerts
|

The occurrence of anti-titin antibodies and thymomas

Abstract: Apart from MG with a thymoma, the finding of the titin autoantibodies was observed to be an exclusive feature of late-onset MG, the frequency being 55%. No data were found to suggest that patients with MG were more likely to present with thymic tumors than other patients exhibiting thymic neoplasia. In about 80%, such tumors in MG were composed of cortical cells. The concept of the anti-titin antibodies merely as a paraneoplastic marker in MG was not supported by these data.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
45
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(47 citation statements)
references
References 31 publications
2
45
0
Order By: Relevance
“…Our estimation, in agreement with other fi ndings [10] , fails to confi rm the balanced ratio of 1 in patients with MG and thymoma as previously suggested [12] . Thymoma was not present in equal proportion in the two sexes across the different age groups.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Our estimation, in agreement with other fi ndings [10] , fails to confi rm the balanced ratio of 1 in patients with MG and thymoma as previously suggested [12] . Thymoma was not present in equal proportion in the two sexes across the different age groups.…”
Section: Discussionsupporting
confidence: 81%
“…The total patient population was signifi cantly weighed in favor of the female patients. According to other studies [3,4,8,10] , the incidence rates disclosed a different age-related incidence pattern in the two genders with an early increase in the third decade in the female sex, and a later increase with age without definite gender preponderance. The results agree with the observation that MG increases with increasing age, emphasizing the importance of MG in the elderly.…”
Section: Discussionmentioning
confidence: 81%
“…Most of the studies included in this review reported on incidence rates for populations in Europe: the rates from 1970 to 2000 varied between 4.1 [13] and 30/1,000,000/ year [14] . Six studies reported on regions outside Europe: Tanzania, Hong Kong, Japan, North America, Cuba and Curaçao and Aruba and the incidence rates found in these areas ranged from 3.0 to 9.1/1,000,000/year.…”
Section: Incidence Rates Geographical Variationmentioning
confidence: 99%
“…In studies of incidence rates in males, the rates increased up to the 60-to 80-year age band in most studies [13,[15][16][17][18][19][20][21][22][23][24][25] , with 2 showing an increase to the 40-year age band [26,27] and 2 reporting fluctuations in rate with age but an overall increase [28,29] . In females, there was more fluctuation in incidence rates with age with some studies showing a peak in incidence at 20-40 years and then a second one at 50-70 years [15, 17, 19-23, 26, 27, 29] , others just had a peak in incidence in the latter age band [13,18,24] . In some studies [13,20,22,25,29,30] the incidence in the elderly (65 or 70 years upwards) was reported to be 0/1,000,000/year, which indicates possible underdiagnosing or misdiagnosing of patients in this group [20,30] .…”
Section: Incidence Rates Geographical Variationmentioning
confidence: 99%
“…Ryanodine receptor antibodies are often associated with malignant thymoma [33]. Apart from MG with thymoma, anti-titin antibodies have been observed to be an exclusive feature of late-onset MG [34].…”
Section: Introductionmentioning
confidence: 99%